The antifungal activity of ethanol extract of red propolis against pathogenic isolates of Candida spp. - Sobreira, Ana Laura de Cabral; Silva, Matheus Merson Araújo; Okamura, Luana Sayuri; Souza, Júlia Beatriz Pereira de; Carmo, Egberto Santos (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2020)
The search for new antifungal substances is necessary, due to the increase in cases of fungal infections in recent years, associated with the appearance of strains resistant to conventional treatments and adverse effects observed during pharmacological therapies. Among these infections, candidiasis stands out, as one of the most common to affect humans. Thus, the objective was to evaluate the antifungal potential of the ethanol extract of red propolis against pathogenic isolates of Candida spp. The Minimum Inhibitory Concentration (MIC) was obtained by using the microdilution, technique in 96-well plates, in which the sensitivity of Candida spp. was evaluated at concentrations of propolis extract in a range from 15,000 µg/mL to 29.3 µg/mL. MIC values were determined by visual analysis of growth inhibition. Then, triphenyltetrazolium chloride (TTC) was added to determine the Minimum Fungicidal Concentration (MFC). All experiments were performed in triplicate. The MIC ranged from 234.4 µg/mL to 937.5 µg/mL, with the species C. albicans being the most sensitive among those tested. The MFC was identical to MIC. From these results, we concluded that the ethanol extract of red propolis showed moderate antifungal activity on most strains of Candida spp., confirming its traditional use regarding its antimicrobial properties, which can be better explored through future pre-clinical and clinical studies.